1st Czecho-Slovak Symposium on Challenges of AI for Administrative Law: “What We Don’t Let Robots Decide?” - Liliia Serhiichuk (Bratislava Law Review, 2025)
AI can make work more efficient and simpler, from automating routine tasks to assisting with more complex decision-making. Its use, therefore, makes sense both in public administration and in public services, where it can improve the quality, accessibility and efficiency of the services provided. The aim is to ensure quality data and a modern digital infrastructure while training employees and ensuring compliance with ethical and security standards. Actions under the strategy include digitisation and automation of public services, training of public administration staff, implementation of ethical and security standards and support for sharing good practice. These measures will lead to faster and more accurate public administration, fairer access to public services, higher quality services and greater citizen trust through the transparent and ethical use of AI.